(untitled) (Contemporary Journal of Social Science Review, 2025)
The Foreign Direct Investment (FDI) is one of the foundations of modern economic growth enabling the formation of capital, the transfer of technologies, employment, and integration into the value chains worldwide . The competition between the states is growing to have quality FDI with the help of stable legal system, predictable policies, and effective institutions . This paper contributes to a comparative legal and policy study of the Singapore investment regime in order to derive lessons that can be transferred to Pakistan. This is because it posits that the Singapore success can not be narrowed down to incentives, but to the system, coordinated architecture of rule-based governance, integrity in institutional coordination, believable dispute resolution, and discipline in anti-corruption enforcement. In comparison, the Pakistani disjointed investment laws, unstable policy, and lax enforcement appear to destroy investor confidence, even with obvious liberalization. The article also presents a novel contribution by showing how selective legal transplantation in place of wholesale imitation would improve the investment governance of Pakistan without compromising regulatory autonomy and sovereignty . It ends with context-related reforms that are based on codification of the investment law, institutional empowerment, arbitration capacity and treaty rationalization that is in line with the current international investment law tendencies.